ROCK1 functions as a critical regulator of stress erythropoiesis and survival by regulating p53 - Vemula, Sasidhar (American Society of Hematology, 2012)
Erythropoiesis is a dynamic, multistep process whereby hematopoietic stem cells differentiate toward a progressively committed erythroid lineage through intermediate progenitors. Although several downstream signaling molecules have been identified that regulate steady-state erythropoiesis, the major regulators under conditions of stress remain poorly defined. Rho kinases (ROCKs) belong to a family of serine/threonine kinases. Using gene-targeted ROCK1-deficient mice, we show that lack of ROCK1 in phenylhydrazine-induced oxidative stress model results in enhanced recovery from hemolytic anemia as well as enhanced splenic stress erythropoiesis compared with control mice. Deficiency of ROCK1 also results in enhanced survival, whereas wild-type mice die rapidly in response to stress. Enhanced survivability of ROCK1-deficient mice is associated with reduced level of reactive oxygen species. BM transplantation studies revealed that enhanced stress erythropoiesis in ROCK1-deficient mice is stem cell autonomous. We show that ROCK1 binds to p53 and regulates its stability and expression. In the absence of ROCK1, p53 phosphorylation and expression is significantly reduced. Our findings reveal that ROCK1 functions as a physiologic regulator of p53 under conditions of erythroid stress. These findings are expected to offer new perspectives on stress erythropoiesis and may provide a potential therapeutic target in human disease characterized by anemia.